+0  
 
+1
85
2
avatar

a3-b3 ist das gleiche wie (a-b)3?

 20.11.2019
 #1
avatar+10778 
+1

Nein, ist es nicht.

laugh

 20.11.2019
 #2
avatar+8704 
+1

\((x-15)^2+(x-5)^2=4\)

 

Ergänzung zu #1

 

\(x^2-30x+225+x^2-10x+25=4\)

\(2x^2-40x+250=4\)

\(x^2-20x+125=2\)

\(x^2-20x+123=0\)

           p           q

\(x=-\frac{p}{2}\pm \sqrt{(\frac{p}{2})^2-q}\)

\(x=10\pm \sqrt{10^2-123 }\)

\(x=10\pm\sqrt{-23}\)
\(x_1=10+\sqrt{23}\cdot i\)

\(x_2=10-\sqrt{23}\cdot i\)

laugh  !

 21.11.2019
bearbeitet von asinus  21.11.2019

9 Benutzer online

avatar
avatar